In Search of a Pathographical Ecopoetics: A Study of Elizabeth Tova Baileyâ€™s The Sound of a Wild Snail Eating - Sarkar, Jayjit; Sarkar, Anik (Journal of Ecohumanism, 2023)
What connects a pathography (an illness narrative) with the school of ecopoetics is poiesis: the Greek for â€œthe act of creationâ€. Pathographical ecopoetics is â€œcreation-withâ€ the natural surroundings during illness. As opposed to Thoreauâ€™s Walden where we find an autobiographical account of oneâ€™s relationship with nature, in pathographical ecopoetics the same relationship is unfolded through pathos (the Greek for â€œpainâ€) and disease. Illness as a method helps in bracketing out our pre-reflective involvement with the natural surroundings and paves the way for newer ways of understanding nature. As opposed to various other intersections between medicine and ecology, like ecopsychology, ecotherapy or green cure, there is a sense of Keatsian spontaneity and aesthetic wonder in pathographical ecopoetics. Elizabeth Tova Baileyâ€™s The Sound of a Wild Snail Eating (2010) is one such account. Her debilitating illness, with â€œsevere neurological symptomsâ€, brings her close to an unremarkable wild snail. Her world starts to get entwined with the world of the snail. The work is a curious admixture of illness memoir, biology, art, environmentalism, and more importantly a deep sense of compassion and empathy for the natural surroundings. The paper will explore the concept of ecopoetics with the help of Baileyâ€™s pathographical account. The Sound of the Wild Snail Eating as a pathographical ecopoetics is away from the techno-scientific gaze of not only modern medicine but modernity in general. Baileyâ€™s world of illness finds effortless connections with the world of the wild snail: her spatial and temporal confinement is attuned to that of the spatio-temporality of the snail. Both the worlds posit a challenge to the speed and â€œhomogeneous, empty timeâ€ of modernity. Both the worlds keep the enchantment and mysteriousness of the natural world alive. In general, the work provides an alternative space in the metanarrative of 21st century modernity and techno-capitalism.